Soil Nutrients in Heterogeneities Land Use in Haui-Luang Headwater Area of the Mekong River - INTASIN, Arita; SOMPONGCHAIYAKUL, Penjai; SINGHRUCK, Patama (Journal of Environmental Management and Tourism; Vol 8 No 5 (2017): JEMT Volume VIII Issue 5(21) Fall 2017, 2018)
Heterogeneity of land uses, difference of agricultural practice ( i.e. fertilizer formula and fertilizer times), seasonal and topography could be affect to quantity of soil nutrients. Level of soil nitrogen and phosphorus are important role for plant growth, thus, assessment content of soil nutrient should be considered for agricultural plan. Huai-Luaung (HL) headwater covers 878 km 2 in the Mekong River of northeast Thailand.  Six distinct land use types are present in the watershed including five that are under cultivation and one is forest. Surface soil samples were collected from 24 sites for chemical analyses with results interpreted using statistics. Level of nitrate (NO 3 -N) and total nitrogen (TN) were decreasing in both times whereas ammonia (NH 4 -N) and available phosphorus (AP) were slightly increase. Soil nitrogen showed significantly difference for both times whereas significant differences among land use categories were found for AP. The results suggest that promotion of appropriate farm management practices is the key in prevention of agricultural non-point sources.